(untitled) (Ustozlar uchun, 2026)
Functionalist approaches in translation studies emphasize the purpose, context, and intended function of a translation rather than strict adherence to the source text. This article explores the theoretical foundations and development of functionalist translation theories, with particular attention to Skopos theory, which asserts that the purpose of a translation should guide the translator’s strategies and decision-making. The study analyzes how functionalist approaches address challenges across different translation domains, including literary, technical, and audiovisual texts, by prioritizing audience expectations, cultural appropriateness, and communicative effectiveness. Additionally, the article examines the implications of functionalist theory for translator training, professional practice, and cross-cultural communication. By integrating theoretical perspectives with practical applications, this study highlights the relevance of functionalist approaches in contemporary translation practice, demonstrating how purpose-oriented translation can bridge linguistic and cultural gaps while achieving intended communicative goals.